ALBY, J. C.; CINER, P.; GARCÍA BAZÁN, B. (2020). Gnosis apócrifa. El conocimiento oculto. Homenaje a Francisco García Bazán. Trotta Guadalquivir, 487 páginas - Durán, Laura Carolina (Oriente y Occidente, 2023)
.